2016
DOI: 10.2147/imcrj.s99230
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic horseshoe-like macular tear: a case report

Abstract: BackgroundAlthough a few cases with idiopathic horseshoe-like macular tear have been reported, the mechanism remains unknown and a standard treatment has yet to be determined.ObjectiveTo report the outcome for a patient with idiopathic horseshoe-like macular tear who underwent vitreous surgery.Case reportA 65-year-old man with no previous injury or ophthalmic disease presented with abnormal vision in his left eye. Best-corrected visual acuity was 0.8 in the right and 0.3 in the left, and the relative afferent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…; Kubota et al. ). In addition, few cases were described after retinal vein occlusion (Karim‐Zade et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Kubota et al. ). In addition, few cases were described after retinal vein occlusion (Karim‐Zade et al.…”
Section: Discussionmentioning
confidence: 98%
“…Horseshoe-shaped macular tears are rare, and the size of the tear is usually relatively large at 0.75 to 1.5 DDs. [ 1 2 3 4 ] It has been reported that severe traction by the vitreous on the retina leads to the macular tears in cases of branch retinal vein occlusion[ 3 ] and idiopathic[ 4 ] horseshoe-shaped macular tears. Karaca et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of an unusual tear called a “horseshoe-shaped macular tear“ have been reported. [ 1 2 3 4 ] These tears can be caused by blunt trauma that leads to a sudden traction by the vitreous on the retina leading to the macular tear. We report a case that had horseshoe-shaped macular tears bilaterally that developed without vitreous traction.…”
mentioning
confidence: 99%
“…The primary causes of vitreous haemorrhage include diabetic retinopathy, branch retinal vein occlusion (BRVO), trauma, retinal tear, rhegmatogenous retinal detachment, and posterior vitreous detachment. 1 3 However, vitreous haemorrhage is rarely caused by a macular tear. To the best of our knowledge, only a few cases of macular tears have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only a few cases of macular tears have been reported in the literature. 1 3 To facilitate better clinical understanding of macular tears, this report describes the details and corresponding etiological analysis of a patient with a giant retinal tear in the fovea.…”
Section: Introductionmentioning
confidence: 99%